Writings On Middle East Of Refik Halid Karay - Hüküm, Muhammed (Fırat University, 2018)
Refik Halid Karay is a well-known writer with his political and social contented newspaper articles as well as having an important place in Turkish story and novels. Refik Halid Karay was exiled two times because of his political attitude. First exile of the writer started in 1913 and ended in 1918. Second exile of Refik Halid started in Beirut in 1922 and ended in 1938. Especially the second exile period lasted in Middle east effected the literary identity of him. His Sürgün [Exile] novel and Gurbet Hikâyeleri [Abroad Stories] are the works focusing on his exile experience in Middle East. 17th book of Memleket Yazıları [Hometown Writings] series named “Sulhte Cimri, Harpte Müsrif [Mean at Peace, Wasteful at War]” of Refik Halid contains political and social analysis about important centers of Middle East geography such as especially Syria, Lebanon, Cyprus, Hatay. These writings are important writings in that they reflect the political and social structure of Middle East after world politics and Ottoman.

Refik Halid Karay, Türk hikâye ve romanında önemli bir yere sahip olmasının yanında siyasi ve sosyal içerikli gazete yazıları ile tanınan bir yazardır. Refik Halid Karay, siyasi tavrı sebebi ile iki kez sürgün hayatı yaşamıştır. Yazarın ilk sürgünlüğü 1913’te başlayarak 1918’de biter. Refik Halid’in ikinci sürgünü ise 1922’de Beyrut’ta başlar ve 1938’de sona erer. Özellikle Ortadoğu’da geçen ikinci sürgün dönemi onun edebi kimliği üzerinde etkili olmuştur. Sürgün romanı ve Gurbet Hikâyeleri Ortadoğu’da yaşadığı sürgünlük deneyimini odağa alan eserlerdir. Refik Halid’in Memleket Yazıları serisinin 17.  kitabı “Sulhte Cimri, Harpte Müsrif” yazarın özellikle Suriye, Lübnan, Kıbrıs, Hatay gibi Ortadoğu coğrafyasının önemli merkezleri hakkında yaptığı siyasi ve sosyal tahlilleri içerir. Bu yazılar dünya siyaseti ve Osmanlı sonrası Ortadoğu’nun sosyal ve siyasi yapısını göstermesi açısından önemli yazılardır.
REFİK HALİD KARAY’IN ORTADOĞU İLE İLGİLİ YAZILARI